Membangun Kepercayaan Pengguna Melalui Transparansi Akad Syariah Sebagai Strategi Peningkatan Penggunaan Fintech Syariah - Ansori, Moh. Asep Zakariya; Wahyudin, M. Wanri; Alawiah, Hanan; Syuardiansyah, Syahra Putri; Suhendri, Suhendri (As-Syirkah: Islamic Economic & Financial Journal, 2026)
The development of Islamic fintech in Indonesia faces user trust challenges despite offering financial services based on sharia principles. This research aims to analyze the influence of sharia contract transparency on user trust and its implications for increasing Islamic fintech usage. The research method employs a literature study with a qualitative approach, analyzing trusted journal articles using keywords "Islamic fintech", "sharia transparency", "user trust", and "sharia-based digital financial innovation". The research findings indicate that sharia contract transparency plays a crucial role in building user trust by providing clear information regarding contract types, transaction mechanisms, rights and obligations, as well as sharia legal foundations. Transparency is capable of reducing risk perception and uncertainty, while simultaneously increasing public sharia financial literacy. Trust functions as a mediating variable that bridges sharia principle transparency with the increase in Islamic fintech usage. This research affirms that contract transparency is not merely a normative obligation, but also an effective business strategy for building long-term relationships with users and strengthening the competitiveness of the Islamic finance industry. Practically, the research findings can serve as a reference for Islamic fintech providers in designing more transparent and accountable operational communication, as well as providing input for regulators in strengthening Islamic fintech governance in Indonesia.